2011
DOI: 10.1093/toxsci/kfr156
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum Proteomics Addressing the Cognitive Deficit of Rats Perinatally Exposed to the Food-Relevant Polychlorinated Biphenyl 138

Abstract: Developmental exposure to polychlorinated biphenyls (PCBs) has been associated with cognitive deficits in humans and laboratory animals by mechanisms that remain unknown. Recently, it has been shown that developmental exposure to 2,2',3,4,4',5'-hexachlorobiphenyl (PCB138), a food-relevant PCB congener, decreases the learning ability of young rats. The aim of this study was to characterize the effect of perinatal exposure to PCB138 on the brain proteome profile in young rats in order to gain insight into the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Reduced mbp expression has also been reported in rats perinatally exposed to polychlorinated biphenyl (Campagna et al. ).…”
Section: Examples Of Dnt Using Zebrafishmentioning
confidence: 74%
See 1 more Smart Citation
“…Reduced mbp expression has also been reported in rats perinatally exposed to polychlorinated biphenyl (Campagna et al. ).…”
Section: Examples Of Dnt Using Zebrafishmentioning
confidence: 74%
“…They found that the expression of mbp but not gfap was significantly decreased in the offspring compared with that in the control offspring. Reduced mbp expression has also been reported in rats perinatally exposed to polychlorinated biphenyl (Campagna et al 2011). A major challenge for DNT is the lack of knowledge of the molecular targets of potential neurotoxicants that results in activation of toxicity pathways and ultimately results in abnormal development .…”
Section: Gene Expression Profilingmentioning
confidence: 98%
“…The neurological impact of PCBs have been comprehensively studied in various animal models of PCB exposure, either as single congeners or mixtures, during different periods of the animal's lifespan [9]. Many of these studies were conducted only on young animals or animals exposed prenatally to PCBs [10,11]. However, a study conducted on adult rats found that spatial learning behavior was altered due to PCB exposure, thereby indicating that PCBs can alter the nervous system in adult animals as well [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Ionexchange and reversed-phase chromatography were found helpful, as well as different affinity chromatography steps (e.g., group-specific enrichment for phosphoproteins; Thingholm et al, 2009). Chromatographic separation of peptide mixtures may also be a versatile step to facilitate protein identification in approaches involving a one-dimensional SDS-PAGE step (Sarioglu et al, 2006;Campagna et al, 2011;Brunelli et al, 2012), when proteins with major abundance tend to mask minor protein components.…”
Section: Liquid Chromatography As a Separation Stepmentioning
confidence: 99%
“…For obtaining quantitative results, they require absolute reproducibility in the peptide separation and a high number of technical replicates, to ensure statistical relevance to the obtained results. In a semiquantitative approach, label-free MS was applied to study the influence of PCB138 on fetal brain proteins (Campagna et al, 2011).…”
Section: Quantitative Msmentioning
confidence: 99%